EFEKTIFITAS PENERAPAN MINDFULNESS DALAM MENGURANGI STRES SISWAKORBAN BULLYING DI MI NW REBAN TEBU - Hartika; Marudin M.Pd.I; Halimatussa'diah M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bullying is a serious issue that still frequently occurs in school environments and has a significant impact on the psychological condition of students. Victims of bullying generally experience stress, anxiety, low self-esteem, and even a decline in learning motivation. One approach that can be used to help address these conditions is mindfulness, which is the practice of full awareness of the present moment consciously and without judgment. The purpose of this study is to describe the effectiveness of implementing mindfulness in reducing stress among students who are victims of bullying at MI NW Reban Tebu. This research employs a qualitative phenomenological approach. Qualitative data were obtained through observation, interviews, and documentation. The results of the study indicate that, theoretically, mindfulness is highly relevant and effective in helping students manage stress caused by bullying, increase self-awareness, and control negative emotions. However, its implementation at MI NW Reban Tebu has not been optimal due to the teachers’ limited knowledge of mindfulness, as well as the absence of specific training and supporting facilities. Nevertheless, simple mindfulness practices such as breathing exercises and self-reflection have been proven to help students become calmer, think more clearly, and gradually build self-confidence. Thus, the application of mindfulness has great potential as a psychological intervention strategy to reduce stress among students who are victims of bullying, provided that it is supported by adequate teacher understanding and appropriate school policies.